Influence of long-term operation on structure, fatigue durability and impact toughness of 09Mn2Si pipe steel; Procedia Structural Integrity; Vol. 5 : 2nd International Conference on Structural Integrity, ICSI 2017, 4-7 September 2017, Funchal, Madeira, Portugal - Panin S. V. Sergey Viktorovich; Vlasov I. V. Ilya Viktorovich; Marushchak P. O. Pavel Orestovich; Eremin A. V. Alexandr Vyacheslavovich; Byakov A. V. Anton Viktorovich; Berto F. Filippo; Vinogradov A. Y. Aleksey Yurjevich; Syromyatnikova A. S. Aytalina Stepanovna; Stankevich R. V. Roman Vladimirovich (2017, 2017)
Title screen